A comparison of trash fish based feed with commercial pellet for Anguilla marmorata Quoy & Gaimard, 1824 at different stocking densities - Truong Minh Ut; Yakupitiyage, Amararatne; Ebbers, Theo; Gallardo, Wenresti G.; IFP - Ford Foundation; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
The study was conducted at Tan Thanh village, Ca Mau province from September to December of 2008 in order to determine technical and economic of eel culture and comparison the growth of eel based on different stocking densities and kind of feeds. Sixty eel farmers were interviewed about technical and economic and constraints of eel culture. The experiment was setup in two factorials such as tilapia trash fish and commercial feed at 3, 6 and 9 ell/mp2 (Bof stocking densities with three replicates in complete block design to investigate the daily weight gain (DWG), specific growth rate (SGR) of eel and feed conversion ratio (FCR). The result showed that the eel farmer was rice farmer formerly and has averaged 2.5 years in eel culture. Almost (100%) eel was fed by trash fish, and the commercial feed was tested on eel culture. The stocking density was averaged 0,47 eel/l mp2 (Bof wild seed, tilapia trash fish and average 14.3 months of period culture, the eel pond culture gives 87% of survival rate, 0.48 kg/l mp2 (Bof yield, 12.7 of FCR, 80% of feed cost in total production cost, US$44,3/1 mp2 (Bof net income and 1.1 of NI/TC ratio. The higher stocking density leads to getting more yield and net income. However, the cost investment efficiency is the same as in different stocking density. Eel farmer face on the difficulties such as lack of trash feed and freshwater in dry season, commercial feed technology do not adapt to eel culture at high price and lack of wild seeds in dry season. In comparison within DWG, SGR and wet matter FCR based on kind of feed and stocking density, there are no interaction between feed type and stocking density, no different among different stocking densities, but these indices of using commercial feed is significant higher than tilapia trash fish. There are interaction between feed type and stocking density in comparison of dry matter FCR and feed cost. Economic effect of FCR in (dry matter) of trash fish is best at stocking density of 6 fishes/mp2 (Bat FCR and feed cost also the same as. Specific pellet feed for eel culture should be studied to reduce trash fish and improve nutrient utilization. The water supply system should be improved to adapt requirement of eel culture in this area. Technology of producing hatchery eel seed is needed to be developed to satisfy seed demand of eel farmer actively to increase economic efficiency.s
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Anguilla (Fish) -- Feeding and feeds